HIV/AIDS in childhood and adolescence. - Cardoso de Paula, Cristiane; Cabral, Ivone Evangelista; Souza, Ivis Emilia de Oliveira; de Brum, Crhis Netto; da Silva, Clarissa Bohrer; Padoin, Stela Maris de Mello (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> Objective. To analyze the theme HIV/AIDS in childhood and adolescence, its characteristics and trends, in Brazilian scientific production between 1983 and 2010. Methodology. Review of 121 quantitative and qualitative descriptive studies. Results. 81% of the production comes from the South-East/South of the country. In the 1980’s, a balance is observed between experience reports (50%) and research (50%). Seventy percent of the papers were produced between 2003 and 2010. The most frequent theme analyzed with regard to childhood was care delivery (75%), against prevention in adolescence (72%). Studies related to HIV/ AIDS in emphasized clinical-epidemiological aspects (70%), while sociocultural studies predominated for the adolescent period (90%), with a preventive trend. Conclusion. The scientific production under analysis is coherent with the Brazilian policy to cope with the epidemic and addresses all care levels related to this public health problem. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->